2003
DOI: 10.1038/sj.onc.1207302
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear–cytoplasmic shuttling of BARD1 contributes to its proapoptotic activity and is regulated by dimerization with BRCA1

Abstract: The breast cancer-associated protein, BARD1, colocalizes with BRCA1 in nuclear foci in the S phase and after DNA damage, and the two proteins form a stable heterodimer implicated in DNA repair, protein ubiquitination, and control of mRNA processing. BARD1 has a BRCA1-independent proapoptotic activity; however, little is known about its regulation. Here, we show that BARD1 localization and apoptotic activity are regulated by nuclear-cytoplasmic shuttling. We identified a functional CRM1-dependent nuclear export… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 27 publications
6
93
0
Order By: Relevance
“…BARD1 is also required for proper localization of BRCA1 to damaged induced foci. This relationship is reciprocal as BRCA1 is required for proper localization of BARD1 (47).…”
Section: Introductionmentioning
confidence: 99%
“…BARD1 is also required for proper localization of BRCA1 to damaged induced foci. This relationship is reciprocal as BRCA1 is required for proper localization of BARD1 (47).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of FL BARD1 and expression of isoforms that lack the RING finger and are deficient for BRCA1 interaction (43) entails the loss of BRCA1-BARD1 ubiquitylation functions, which are important for tumor suppressor functions but will also influence BRCA1 stability and/or nuclear localization (44)(45)(46). Therefore, lack of FL BARD1 and expression of isoforms lacking the RING domain could have a similar cancer predisposition effect as mutations in BRCA1 when occurring in healthy tissue.…”
Section: Bard1 Isoforms In Cancermentioning
confidence: 99%
“…Recently, it was shown that BRCA1 contains a functional HIV Rev-like NES within its N-terminus (aa 86-95) (Rodriguez and Henderson, 2000;Rodriguez et al, 2004) (see Table 1). This region of BRCA1 also contains a corepressor extended helix-like motif, LxxI(I/ H)xxx(I/L) (Perissi et al, 1999).…”
Section: Role Of Brca1 Nuclear Export Signal (Nes)/ Corepressor-like mentioning
confidence: 99%